Information Technology and Organizational Culture as Determinants of Accounting Information System Effectiveness - Rachman, Gun Gunawan; Nurdiyanti, Nurdiyanti; Nurcholisah, Kania (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
This study aims to analyze the influence of information technology and organizational culture on the effectiveness of the accounting information system at PT. Bozzetto Indonesia. In the digital era, the role of information technology is crucial in supporting the efficiency and effectiveness of accounting information systems. Organizational culture also plays a significant role in shaping employee behavior and work patterns that support the system’s success. This research adopts a quantitative approach, with data collected through questionnaires distributed to 37 respondents. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show that both information technology and organizational culture have a positive and significant effect on the effectiveness of the accounting information system. These findings emphasize the importance of integrating technology and organizational values in supporting the effective and efficient management of accounting information. This research contributes theoretically to the development of accounting knowledge and provides practical implications for companies to optimize the performance of their accounting information systems.